Bioestimulantes radiculares en el cultivo de piña de exportación variedad Md-2 (Ananas comosus) en la provincia Santo Domingo de los Tsachilas. - Solórzano Cedeño, Juan Miguel (2013)
The research was conducted in the company TERRASOL SA located in the parish San Jacinto Búa, Canton Santo Domingo de los Colorados, the coordinates are 00° 12' 52" South latitude and 79º 18' 49" west longitude, at a height above sea level of 349 m. The investigation lasted 90 days. As a general objective the effect of root bio-stimulants in growing export pineapple MD-2 variety (Ananas comosus) in the province of Santo Domingo Tsachilas evaluated. 800 plants as experimental unit in each of the plots in four replications were used for a total of 3200 seedlings per treatment and 16000 for the full trial, a randomized complete design (DBCA) blocks with five treatments and four replications to determine differences between treatment means the multiple range test of Tukey (p < 0.05) as likely to use. The variables were evaluated at the fifth and eighth week. In the fifth week in fresh weight variable is numerically superior T2 ( MKP 40 kg / ha) treatment, with values of 379.0 g . For variables root weight, length of primary root and primary root mortality exceeds the T5 (absolute control) treatment with 4.2 g, 13.7 g and 2.4 respectively dead roots. The highest number of roots was for T4 (Rooting 1.5 Lt / Ha) treatment, with an average of 5.9 roots. In the eighth week in the variable fresh weight (g) exceeds the T5 (absolute control) treatment with 485.9 g. In the variable dry weight (g) is numerically higher MKP treatment T2 (40 kg / ha) with 68.7 g. For variables root weight (g), number of roots and primary root length (cm) is higher ENEROOT T3 treatment (2 Lt / Ha + MKP 40 Kg / ha) with values of 14.6 g, 12.6 roots and 26.8 cm respectively. No mortality of primary roots was presented in any of the treatments under study. In the weeks assessed by performing monitoring pests are not present as sypmhylans, Cochineal, borers and molluscs. Keywords: bioestimulantes root, pineapple MD-2 variety.